Textile production in pre-Roman Italy - Gleba, Margarita (Ancient textiles series, 2008)
Older than both ceramics and metallurgy, textile production is a technology which reveals much about prehistoric social and economic development. This book examines the archaeological evidence for textile production in Italy from the transition between the Bronze Age and Early Iron Ages until the Roman expansion (1000-400 BCE), and sheds light on both the process of technological development and the emergence of large urban centres with specialised crafts. Margarita Gleba begins with an overview of the prehistoric Appennine peninsula, which featured cultures such as the Villanovans and the Etr.